2016
DOI: 10.3389/fcell.2016.00108
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol Kinases (DGKs): Novel Targets for Improving T Cell Activity in Cancer

Abstract: Diacylglycerol kinases (DGKs) are a family of enzymes that catalyze the metabolism of diacylglycerol (DAG). Two isoforms of DGK, DGKα, and DGKζ, specifically regulate the pool of DAG that is generated as a second messenger after stimulation of the T cell receptor (TCR). Deletion of either isoform in mouse models results in T cells bearing a hyperresponsive phenotype and enhanced T cell activity against malignancy. Whereas, DGKζ appears to be the dominant isoform in T cells, rationale exists for targeting both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 63 publications
4
37
0
Order By: Relevance
“…In particular, our screen showed that knockdown of diacylglycerol kinase (DGK) family of genes resulted in increased sensitivity to CAR-T cells. Previous groups have shown that inhibition of DGK-α activity in T cells using pharmacological inhibitors induced T cell activation, thus improving its cytotoxic activity on cancer cells (33,38). Our study indicates that knockdown of DGK kinases in myeloma cells increases sensitivity to T cells.…”
Section: Bcma Car-t Cell Co-culture Screen Reveals Myeloma Cell-intrisupporting
confidence: 59%
“…In particular, our screen showed that knockdown of diacylglycerol kinase (DGK) family of genes resulted in increased sensitivity to CAR-T cells. Previous groups have shown that inhibition of DGK-α activity in T cells using pharmacological inhibitors induced T cell activation, thus improving its cytotoxic activity on cancer cells (33,38). Our study indicates that knockdown of DGK kinases in myeloma cells increases sensitivity to T cells.…”
Section: Bcma Car-t Cell Co-culture Screen Reveals Myeloma Cell-intrisupporting
confidence: 59%
“…These include therapies that target other immune checkpoint receptors such as Tim3 and Lag3 (2), or other inhibitory receptors including the adenosine 2A receptor, prostaglandin E 2 (PGE 2 ) receptor, and TGFβ receptor complex (7, 8). Recently, interest has developed regarding the possibility of targeting intracellular inhibitory proteins to improve T cell activity against cancer, including diacylglycerol kinase ζ (DGKζ) (9, 10), and Casitas b-lineage proto-oncogene b (Cbl-b) (11), which attenuate signal transduction events downstream of the T cell receptor (TCR) and CD28. Targeting these proteins may be superior to targeting cell surface proteins, since their elimination confers simultaneous insensitivity to multiple cell surface inhibitory receptors.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we analyzed the antitumor efficacy of T cells that are deficient in diacylglycerol kinase zeta (DGKz), which is a key regulator of the cell membrane lipid diacylglycerol (DAG). DGKs are a family of proteins that phosphorylate DAG, resulting in decreased levels of this molecule, which is important in lipid biochemistry and signal transduction in eukaryotic cells (6,7). In T cells, DAG functions as an important second messenger, participating in the activation of RasGRP1 and PKCq after stimulation of the T-cell receptor (TCR; ref.…”
Section: Introductionmentioning
confidence: 99%